Damping analysis of a quad beam MEMS piezoresistive accelerometer. (4th July 2021) - Jency, J. Grace; Sekar, M.; Sankar, A. Ravi
ABSTRACT: This article presents the simulation and experimental validation of damping for an MEMS (micro-electromechanical systems) piezoresistive accelerometer with an optimized mass dimension and air gap. A commercially available device should be able to withstand acceleration shock having a full-scale range of at least from 100 g to 1000 g irrespective of its nominal operation range. To achieve this, a micromachined silicon accelerometer is bonded with top and bottom Pyrex glasses. These glass plates provide viscous damping to the proof mass during its movement influencing the performance of the accelerometer. To improve the damping characteristics, the proposed accelerometer device is electroplated with gold on top of the device and an optimum distance of 27 µm is maintained between top/bottom glasses. It is observed that the vibrations are detected in a much earlier stage when the device is electroplated with gold with an optimum air gap distance of 27 µm. Experimental results prove an optimized air gap device for an electroplated gold with a proof thickness of 170 µm as a reduction of 23.26% from the resonant peak of electroplated gold device with a proof thickness of 270 µm. This device aims to design a typical air craft sensing motion application.